PEMANFAATAN SAMPAH KULIT DURIAN (DURIO ZIBETHINUS) MENJADI BAHAN BAKU BIO-BATERAI RAMAH LINGKUNGAN - Salsabila, Annisa; Putri, Desi Az Zahra; Ambomasse, Nurfadila M (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Universitas Jember, 2024)
This research aims to reduce durian skin waste by making bio-battery raw materials that are environmentally friendly. In addition, this research also aims to test the effectiveness of the battery by testing voltage, current, and power. This research is experimental research with the method used observation and measurement. Based on the results obtained, pasta batteries with variations in the ratio of durian peel mass and electrolyte mass produce varying voltages and electric currents. The optimal variation is in the first combination with 5 grams of durian peel and 20 grams of electrolyte, which produces the highest power of 4.50 Watts. There is no significant effect between the mass of durian peel and the mass of electrolyte on the voltage and current of the paste battery. Paste batteries with full durian produce lower voltage, amperage, and power compared to paste batteries with variations in the ratio of durian peel mass and electrolyte mass.